2008
DOI: 10.1086/591072
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Oxygen‐Bearing Molecules in the Interstellar Medium and in Planetary Atmospheres: Cyclopropenone (c‐C3H2O) and Propynal (HCCCHO)

Abstract: We investigated the formation of two C 3 H 2 O isomers, i.e., cyclopropenone (c-C 3 H 2 O) and propynal (HCCCHO), in binary ice mixtures of carbon monoxide (CO) and acetylene (C 2 H 2 ) at 10 K in an ultrahigh vacuum machine on highenergy electron irradiation. The chemical evolution of the ice samples was followed online and in situ via a Fourier transform infrared spectrometer and a quadrupole mass spectrometer. The temporal profiles of the cyclopropenone and propynal isomers suggest (pseudo-) first-order kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 54 publications
0
36
0
Order By: Relevance
“…The infrared spectra can also be exploited to identify functional groups such as those related to complex organic molecules (COMs) like carbonyl groups associated with aldehydes, ketones, and carboxylic acids (Socrates 2004). However, different molecules with the same functional groups will have similar vibrational frequencies differing by a few 10 cm −1 causing overlap in the infrared spectra observed; this limits the identification of individual molecules (Bennett et al 2005b;Zhou et al 2008). Due to these restrictions, FTIR aids in identifying small molecules and new functional groups of organics formed within the astrophysical ice analogs, but FTIR cannot always identify specific molecules of interest; therefore, the exclusive assignment of a single molecule to infrared bands in an unknown mixture of molecules is not advisable as many vibrational frequencies may overlap.…”
Section: Introductionmentioning
confidence: 99%
“…The infrared spectra can also be exploited to identify functional groups such as those related to complex organic molecules (COMs) like carbonyl groups associated with aldehydes, ketones, and carboxylic acids (Socrates 2004). However, different molecules with the same functional groups will have similar vibrational frequencies differing by a few 10 cm −1 causing overlap in the infrared spectra observed; this limits the identification of individual molecules (Bennett et al 2005b;Zhou et al 2008). Due to these restrictions, FTIR aids in identifying small molecules and new functional groups of organics formed within the astrophysical ice analogs, but FTIR cannot always identify specific molecules of interest; therefore, the exclusive assignment of a single molecule to infrared bands in an unknown mixture of molecules is not advisable as many vibrational frequencies may overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high activation energy, the reaction of acetylene and carbon monoxide is unlikely to proceed in the conditions found within interstellar environment. However, this reaction could be driven by radiation exciting the reactants from the ground to an excited electronic state (Zhou et al 2008). In this work, we focused on the neutral-neutral reactions where c-C 3 H 2 detected in the same region of space as c-H 2 C 3 O is assumed to be the parent molecule of c-H 2 C 3 O.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high barrier, the value of the rate constant of this reaction is effectively zero, even at relatively high temperatures. Despite the high barrier for this gas phase reaction, Zhou and coworkers (Zhou et al 2008) were able to synthesize cyclopropenone from electronically excited acetylene and carbon monoxide on the surface of icy grains. They demonstrated that if either carbon monoxide or acetylene is excited to the first electronic excited state the reaction becomes barrierless.…”
Section: Reaction (3): Acetylene and Carbon Monoxidementioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al (2008) studied the non-equilibrium grain-ice chemistry in cold (∼10 K) regions of the ISM, finding that cyclopropenone is formed on grain surfaces via reactions between triplet CO and C 2 H 2 , i.e., and that propynal is formed in the bulk by carbon monoxide and acetylene through a radical pair reaction, i.e., Zhou et al (2008) found that cosmic ray protons (∼10 MeV) are likely the source of energy that drives these reactions, inducing a C-H cleavage in collisions with acetylene that initiates reactions (1) and (2). Experimental results from ultra-high vacuum irradiation of ice samples showed that the two metastable isomers of C 3 H 2 O were produced, with only a tentative detection of propadienone.…”
Section: Formation Chemistry On Grain Surfacesmentioning
confidence: 99%